Kriopreservasi Semen Domba Garut dengan Pengencer Tris yang Disuplementasi Ethylene Diamine Tetraacetic Acid (CRYOPRESERVATION OF GARUT RAM SEMEN WITH TRIS EXTENDER ETHYLENEDIAMINETETRAACETIC ACID) - Rizal, Muhammad; ., Herdis; ., Nasrullah; Riyadhi, Muhammad; Sangadji, Insun; ., Yulnawati (Jurnal Veteriner, 2015)
Ethylene diamine tetraacetic acid (EDTA) is a molecular structure that binds to heavy metals andother toxins which needed to protect the spermatozoa during the cryopreservation process. The objectiveof this research was to examine EDTA in maintain the quality of garut ram frozen semen. Semen werecollected from mature Garut ram by artificial vagina. Fresh semen were evaluated and divided in equalvolume into three tubes and diluted with Tris extender containing 20% egg yolk (TEY-20) as control, TEY-20 + 0.01% EDTA (EDTA0.01), and TEY-20 + 0.02% EDTA (EDTA0.02), respectively. Semen was loaded in 0.25 mL mini straw with the concentration of 100 million motile spermatozoa. Semen was equilibrated at5oC for three hours, then frozen and stored in liquid nitrogen container. Quality of spermatozoa includingpercentages of motile spermatozoa (MS), live spermatozoa (LS), and intact plasma membrane (IPM) wereevaluated after diluting, equilibrating, and thawing. Data were analyzed using completely randomizeddesign with three treatments and five replicates. Means were compared significant difference test at 0.05significant level. Results of this research showed that mean volume, color, consistency, pH, mass movement,spermatozoa concentration, percentage of MS, percentage of LS, percentage of abnormal spermatozoa,and percentage of IPM of garut ram fresh semen were 0.87 mL, cream, thick, 6.98, 3, 4,296 million cell/mL,75%, 86.33%, 4.4%, and 85%, respectively. Percentages of MS, LS, and IPM after thawing in control (42.5,52.5, and 52.17%) was not significantly difference with EDTA0.01 (44.17, 52.5, and 52.5%) and EDTA0.02(39.17%, 51%, and 48.33%). In conclusion, the addition of EDTA in Tris extender can maintain quality ofGarut ram frozen semen, and its suitable using in artificial insemination program. Addition of EDTA cannot enhancing quality of garut ram frozen semen.
Keywords: cryopreservation, EDTA, frozen semen, Garut ram